IMPROVING STUDENTS' LEARNING OUTCOMES THROUGH PJBL LEARNING MODELS IN PRACTICES FOR MAKING OF CASTING TAPE (Manihot utilissima) WITH THE ASSISTANCE OF MEDIA QUIZIZ - Ade Daud Saepul; Nina Helina; Yoyon Sutresna (Journal Of Biology Education Research (JBER), 2023)
Learning is a process of changing behavior so that knowledge and skills are obtained to be better than before. Factors that influence the quality of an educational program include the quality of students, the availability of teaching materials, curriculum, facilities/infrastructure, class and school management, and so on. This study aims to prove that the project based learning model with quizizz media can improve student learning outcomes. This research is a class action research using a project-based learning model with the help of Quizzz. This research was conducted through two cycles. Luckily, the students seemed happy to carry out this project based learning and they started to do it in collaboration. Then collaboration grew the respinsibility from each of them. Therefore it will have a positive impact on student progress. Moreover, it is true that the result gave an increase in student learning activities and student learning outcomes. The conclusion of this study is that the project based learning model with the help of Quizizz has succeeded in increasing student learning outcomes.